PC Hardware in a Nutshell, 2nd Edition - Thompson, Barbara Fritchman (O'Reilly, 2011)
Carefully researched and written, PC Hardware in a Nutshell, 2nd Edition is packed with useful and unbiased information, including how-to advice for specific components, ample reference material, and a comprehensive case study on building a PC. To the point yet complete, this book provides an enormous amount of timeless information intended for anyone who buys, builds, upgrades, or repairs PCs in a corporate, small business, or home setting.